Design and Construction of Mini 3D Printer - Soeatuptim, Jaratsri; Chaijit, Seksan (Journal of Advanced Development in Engineering and Science, 2023)
This article proposes the design and construction of a Mini 3D printer. A principle of 3D molding machine by using Fused Deposition modeling (FDM) technology is studied. A diameter 1.75 mm of Acrylonitrile Butadiene Styrene (ABS) filament was used when the maximum capacity size of width 1,500 mm x length 1,500 mm x height 1,000 mm can be formed for 3D geometry model including rectangular shape, triangular shape and cylindrical shape. The tolerance of X-axis and Y-axis position is ± 5% and tolerance of Z axis position is ± 10 %. The 3D printing machine uses G-code, made by encoding 3D model into G-code to operate machine and molding 3D model. Molding resolution can be changed in designing software with negative proportional change of error. This machine was tested by molding three dimensions of width 20 mm หรือ mm x length 20 mm x height 20 mm rectangular, triangular and cylindrical geometry models. The experiment result of the rectangular shape model had percent relative error for X-axis of 0.7%, Y-axis of 1.0%, and Z-axis of 0.3% with molding time for 14 seconds. The triangular shape model had percent relative error for X-axis of 0.3%, Y-axis of 0.5%, and Z-axis of 0.1% with molding time for 12 seconds. The cylindrical shape model had percent relative error for X-axis of 0.3%, Y-axis of 0.5% and Z-axis of 0.1% with molding time for 11 seconds.